Life Satisfaction Among Turkish and Moroccan Immigrants in the Netherlands: The Role of Absolute and Relative Income - DUMLUDAĞ, DEVRİM (SPRINGER, 2012)
In this paper we investigate the role of several socio-economic and non-economic factors such as absolute and relative income, education and religion to explain the differences of happiness levels of Turkish and Moroccan Immigrants in the Netherlands by using ordered logit model. We focus on members of the Moroccan and Turkish communities, as these are the two largest non-EU immigrant communities in the Netherlands. Our findings reveal that Moroccans, although they have lower income levels and higher unemployment rates than Turkish immigrants, their happiness level is higher than the Turkish immigrants. In order to understand this dilemma a questionnaire survey was performed to 111 Turkish and 96 Moroccan immigrants in Rotterdam, Amsterdam, Den Haag, Utrecht and Arnhem in 2010. The main purpose is to investigate how reference group's self-reported life satisfaction is related to the level of absolute income; the level of relative income and other socio-economic factors. The main findings are that for Turkish sample relative income is significantly and negatively correlated with life satisfaction whereas, both absolute income (positively) and relative income (negatively) are significantly correlated with life satisfaction for Moroccan case.
Keywords: Life satisfaction; Immigrants; Ordered logit model; Relative income; HAPPINESS; 2ND-GENERATION; DISCRIMINATION; ADOLESCENTS; MIGRATION